Experimental evidence of the relative effectiveness of problem-based learning for knowledge acquisition and retention. Issue 8 (16th November 2016) - Wijnen, Marit; Loyens, Sofie M. M.; Schaap, Lydia
Abstract : This study investigated the effects of problem-based learning (PBL) on knowledge acquisition and knowledge retention in a controlled experiment in a lab setting. Eighty-eight first-year psychology students were randomly assigned to either a PBL condition, a lecture condition, or a self-study condition. All participants had the opportunity to study the same text. Their knowledge acquisition was tested on both an immediate post-test and a delayed post-test, one week later. The results showed beneficial effects for the PBL group on the immediate and the delayed test compared to the lecture group. There were no differences between knowledge acquisition scores for the self-study condition and either of the other conditions. Moreover, no differences on knowledge retention were shown, because the decline in performance over time was equal in all conditions. In conclusion, the present study provides experimentally based evidence of the disadvantageous effects of instruction through lectures compared to PBL.